Students' Numeracy Skills in Learning Cartesian Coordinate System Using PMRI in the Context of Palembang LRT - Nadiati Amarta; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Jurnal Pendidikan Matematika, 2023)
This research aims to describe the numeracy skills of eighth grade students in learning Cartesian coordinate system using the approach of realistic mathematics education in the Indonesian context, or PMRI, by using Palembang Light Rail Transit (LRT) context. This research is a descriptive qualitative research and the research participants were students who belonged to class 8 of secondary school (SMPN) 59 Palembang. Tests and interviews with students were the data collection techniques used, and the written examination comprised two questions designed to measure the students' proficiency in mathematics. From the analysis and discussion of the students' responses, it was found that there were 11 high ability students (39.29%), eight middle ability students (52.14%), and nine low ability students (32.14%). Interviews were conducted to clarify the responses of the students. The interviews revealed that the main cause of the students' difficulties was a lack of concentration while attempting to answer the numeracy test questions. It is concluded that the students of SMPN 59 Palembang demonstrated adequate numerical skills in solving the test problems related to the Cartesian coordinate system using the PMRI approach in the context of Palembang LRT.